Serum bactericidal activity against multi-drug resistant Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa - Chowdhury, Melisha; Prova, Sadiba Salim (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.